2015
DOI: 10.1159/000375481
|View full text |Cite
|
Sign up to set email alerts
|

Single Bilateral Dexamethasone Implant in Addition to Panretinal Photocoagulation and Oral Azathioprine Treatment in IRVAN Syndrome

Abstract: The idiopathic retinal vasculitis, aneurysms and neuroretinitis (IRVAN) syndrome is a disease characterized by multiple retinal macroaneurysms, neuroretinitis and peripheral capillary nonperfusion. Visual loss may result from either ischemia-related complications or macular involvement. Treatment is not always rewarding. We report a case with stage 2 IRVAN syndrome who was successfully treated with a single bilateral intravitreal dexamethasone implant in addition to panretinal photocoagulation and systemic aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…The role of steroids also remains unclear. Saatci et al 63 used bilateral dexamethasone implants with oral immunosuppressants in the form of azathioprine tablets and PRP for treating a case of IRVAN. Empeslidis et al 64 administered a unilateral dexamethasone implant to combat persistent macular edema despite previous PRP, oral steroid treatment, and pars plana vitrectomy in a patient with stage 3 IRVAN syndrome.…”
Section: Treatmentmentioning
confidence: 99%
“…The role of steroids also remains unclear. Saatci et al 63 used bilateral dexamethasone implants with oral immunosuppressants in the form of azathioprine tablets and PRP for treating a case of IRVAN. Empeslidis et al 64 administered a unilateral dexamethasone implant to combat persistent macular edema despite previous PRP, oral steroid treatment, and pars plana vitrectomy in a patient with stage 3 IRVAN syndrome.…”
Section: Treatmentmentioning
confidence: 99%
“…Saatci et al [6] reported resolution of ME and posterior pole exudates with a dexamethasone implant in a patient with systemic immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical characteristics are divided into major criteria (retinal vasculitis, aneurysmal dilation at the bifurcations, neuroretinitis) and minor criteria (peripheral retinal ischemia, retinal neovascularization, macular exudations) [1,2] the evolution is variable, which can in some cases lead to decrease in the visual and anatomical prognosis of the eye despite the different therapeutic modalities that are reported [2][3][4][5] There is a classification that was developed to stage the progression of the disease (Table 1) [2]. Imaging makes it possible to follow up and get accurate information on the evolution [6], fluorescence angiography makes it possible to detect aneurysmal vascular anomalies, retinal neovascularizations, peripheral capillary ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…There is no common therapeutic consensus to date, multiple therapeutic options have been reported: from simple observation [5,8] to pan retinal photocoagulation which is one of the most effective treatments for controlling macroanurysms and ischemia [2,17], corticosteroid therapy in the form of a dexamethasone implant to combat macular edema with a significant reduction in thickness, thus improving vision, intravitreal injection of anti VEGF [4,9,[10][11][12][13][14][15], administration of the Infliximab immunomodulator to treat exudation [9,10] surgery comes last for treatment of advanced stages with vitrectomy and traditional detachment surgery or epimacular membrane peeling…”
Section: Discussionmentioning
confidence: 99%